THE SIGNIFICANCE OF AXILLARY BLOCK IN UPPER ARM AMPUTATION IN A PATIENT WITH SERIOUS COMORBIDITIES: A CASE REPORT - Nikolic, Aleksandar; Damnjanovic, Zoran; Stepanovic, Nemanja; Damnjanovic, Goran; Ristic, Uros; Vasilijic, Milena; Stosic, Marija; Zivadinovic, Jelena; Stojanovic, Marko; Rancic, Dejan; Djordjevic, Miodrag (Acta medicae Medianae, 2025)
Surgical management is sometimes the only viabletreatment option for patients with peripheral arterial occlusive disease.However, performing surgery under general endotracheal anesthesia in patientswith hemodynamic and respiratory instability poses a significant challenge. Insuch cases, neuraxial blocks may provide a safer alternative. An 80-year-old male patient was urgently admitted tothe Department of Internal Medicine at the Military Hospital Niš due todifficulty breathing and a livid discoloration of the left hand and forearm.Carpal pulses were absent, and the patient had experienced loss of movement andsensation in the hand for several days. Clinical examination and Multislicecomputed tomographc angiography of the pulmonary and major arteries of the leftarm confirmed a diagnosis of pulmonary embolism and occlusion of the subclavianand brachial arteries. After evaluating the patient’s condition, theanesthesiologist opted for a neuraxial block instead of general endotrachealanesthesia.Avoiding general endotracheal anesthesia andutilizing neuraxial blocks could minimize the possibility of adverse events inhigh-risk patients.
Keywords: neuraxial anesthesia, pulmonary embolism, peripheral arterial occlusive disease